2016
DOI: 10.1021/acs.jpcb.5b11076
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Studies of Unlabeled Full-Length p53 Protein Binding to DNA

Abstract: p53 is an anti-tumor protein that plays an important role in apoptosis, preserving genomic stability and preventing angiogenesis, and it has been implicated in a large number of human cancers. For this reason it is an interesting target for both fundamental studies, such as the mechanism of interaction with DNA, and applications in biosensing. Here, we report a comprehensive study of label-free, full length p53 (flp53) and its interaction with engineered double-stranded DNA in vitro, at the single-molecule lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…While bimolecular spots (the right arrow), whose representative cross-section profile is shown in the right inset ( Figure 3B), likely correspond to dimers of p53, in agreement with literature data that reported the presence of p53 dimers at similar concentrations. 33 The height of the p53 images is significantly lower than that obtained for COP1 molecules, according to the lower MW of p53 protein with respect to COP1.…”
mentioning
confidence: 88%
“…While bimolecular spots (the right arrow), whose representative cross-section profile is shown in the right inset ( Figure 3B), likely correspond to dimers of p53, in agreement with literature data that reported the presence of p53 dimers at similar concentrations. 33 The height of the p53 images is significantly lower than that obtained for COP1 molecules, according to the lower MW of p53 protein with respect to COP1.…”
mentioning
confidence: 88%
“…The tumor suppressor protein p53 is a widely distributed phosphoprotein that is the central player in the pathways controlling cell growth, DNA repair, cell differentiation, senescence, and apoptosis [ 1 , 2 , 3 , 4 , 5 , 6 ]. It is found that over 50% of human cancers are associated mutations in the p53 protein [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor suppressor protein p53 is a widely distributed phosphoprotein that is the central player in the pathways controlling cell growth, DNA repair, cell differentiation, senescence, and apoptosis [ 1 , 2 , 3 , 4 , 5 , 6 ]. It is found that over 50% of human cancers are associated mutations in the p53 protein [ 1 ]. The p53 protein is a flexible multidomain protein containing 393 residues in full length, and consists of four distinct domains: (a) the unstructured N-terminal trans-activation domain (N-ter) and a proline-rich domain, which can bind to a series of proteins and regulates p53 transcription [ 7 ] and dissociation from DNA [ 8 ]; (b) the central core region known as the DNA-binding domain (DBD), which regulates the specific binding to DNA [ 9 ]; (c) the tetramerization domain (Tet) and (d) the C-terminal domain (C-Ter) which has been shown to bind nonspecifically to DNA [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It does not rule out that the observed scaling behavior is a property of the polymer itself, but the present model does offer an explanation that reconciles differences in scaling factors observed with the same analyte (DNA), but with different platforms or experimental contexts. In fact, surface effects have been shown to have a significant impact on the translocation of proteins and protein/DNA complexes, 36,37 and it is also well-known that the interaction between DNA and a surface is strongly dependent on the electrolyte composition. 38 To this end, the presence of Mg 2+ results in the adsorption of DNA to mica, while preserving some strand mobility when bound to the surface (i.e.…”
mentioning
confidence: 99%